A Study on Factors that contribute to Employee Engagement in I.T. Companies in Indore - Kukrety, Deepti Bajpai; Joshi, Rajshree (International Journal of Psychosocial Rehabilitation, 2020)
Employee engagement first appeared as a concept in management theory in the 1990s, becoming widespread as a management practice in the 2000s. Employee engagement is the degree of commitment and involvement an employee has towards their organization and its vision, mission, objectives and values. An engaged employee is aware of business constructs and works with peers to enhance performance for the benefit of the organization. It is a positive attitude that employees carry towards the organization and its values. The paper focuses on how employee engagement is a precursor of job involvement and what I.T. Company’s should do to create an atmosphere that keep employees engaged.